Cationizable lipid micelles as vehicles for intraarterial glioma treatment - Nguyen, Juliane (J Neurooncol, 2016)
The relative abundance of anionic lipids on the surface of endothelia and on glioma cells suggests a workable strategy for selective drug delivery by utilizing cationic nanoparticles. Furthermore, the extracellular pH of gliomas is relatively acidic suggesting that tumor selectivity could be further enhanced if nanoparticles can be designed to cationize in such an environment. With these motivating hypotheses the objective of this study was to determine whether nanoparticulate (20 nm) micelles could be designed to improve their deposition within gliomas in an animal model. To test this, we performed intra-arterial injection of micelles labeled with an optically quantifiable dye. We observed significantly greater deposition (end-tissue concentration) of cationizable micelles as compared to non-ionizable micelles in the ipsilateral hemisphere of normal brains. More importantly, we noted enhanced deposition of cationizable as compared to non-ionizable micelles in glioma tissue as judged by semiquantitative fluorescence analysis. Micelles were generally able to penetrate to the core of the gliomas tested. Thus we conclude that cationizable micelles may be constructed as vehicles for facilitating glioma-selective delivery of compounds after intraarterial injection.